Mechanical performance of 3D printed functionally graded PETG: An experimental investigation - Sheikh Aadil Hussain; M.S. Charoo; Mir Irfan Ul Haq (Next Materials)
Fused Deposition Modeling (FDM), a widely used 3D printing technique, has emerged as a suitable technology for developing Functionally Graded Materials (FGMs) due to its capability to fabricate complex geometries and structures. The objective of this study is to compare the mechanical properties of functionally graded additively manufactured (FGAM) samples with those of non-functionally graded samples. The influence of various process parameters, specifically infill densities (60 %, 80 %, and 100 %) and infill patterns (gyroid, cubic, and octahedral) on mechanical properties such as tensile strength, flexural strength, compressive strength, and impact energy were investigated using polyethylene terephthalate glycol (PETG) FGAM samples. Two categories of samples were printed: non-FGAM samples with uniform infill density and pattern, and FGAM samples with three varying infill densities and patterns sequentially distributed through the sample thickness. Results indicate that functionally graded specimens with multi-pattern configurations exhibit the highest ultimate tensile strength, showing a 12 % improvement compared to non-FGAM G100 samples. Similarly, in flexural testing, the multi-pattern FGAM specimen P1 demonstrated the best performance, with a 22 % improvement over its non-FGAM counterpart G100. Compression testing also showed a similar trend, where specimen P1 achieved the highest performance, improving by approximately 10 % compared to the non-FGAM specimen G100. Scanning Electron Microscopy (SEM) analysis revealed strong inter-raster bonding and well-formed microstructures with minimal flaws and voids in the gyroid and functionally graded samples at 100 % infill. In contrast, samples with the octahedral pattern exhibited larger voids, poor layer adhesion, and delamination, likely contributing to their reduced strength. This study suggests that tailoring materials by varying infill density and pattern can significantly enhance mechanical performance, offering promising potential for the development of high-strength engineering components for structural applications.